Limitations of observational data in interpreting SPRINT results - Kenny, Rose; Sexton, Donal (My University, 2018)
We read with interest the Research Letter in a recent issue of JAMA Internal Medicine by Sexton et al 1 on the rates of syncope and injurious falls in Irish Longitudinal Study of Aging (TILDA) participants 75 years or older meeting eligibility criteria for the Systolic Blood Pressure Intervention Trial (SPRINT). Their work highlights the principle that clinical trials are a starting point for therapeutic discussions but that medical care much be individualized to the patient’s estimated risk. However, there are several important differences between these 2 studies that merit discussion when considering the higher rates of syncope and injurious falls observed in TILDA.
PUBLISHED
Keywords: Ageing